2012
DOI: 10.14712/23362936.2015.37
|View full text |Cite
|
Sign up to set email alerts
|

Blockade of the Ganglion Impar (Walther), Using Ultrasound and a Loss of Resistance Technique

Abstract: The ganglion impar is an unpaired sympathetic structure located at the level of the sacrococcygeal joint. Blockade of this structure has been utilised to treat chronic perineal pain. Methods to achieve this block often involve the use of fluoroscopy which is associated with radiation exposure of staff involved in providing these procedures. We report a combined loss of resistance injection technique in association with ultrasound guidance to achieve t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
5
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 14 publications
(7 citation statements)
references
References 11 publications
2
5
0
Order By: Relevance
“…Firstly, in our study, the ultrasound-guided method was roughly consistent with that reported by Johnston et al [ 16 ]. Local, clear ultrasonograms were obtained by Johnston et al [ 16 ], who used high-frequency probes.…”
Section: Discussionsupporting
confidence: 91%
See 2 more Smart Citations
“…Firstly, in our study, the ultrasound-guided method was roughly consistent with that reported by Johnston et al [ 16 ]. Local, clear ultrasonograms were obtained by Johnston et al [ 16 ], who used high-frequency probes.…”
Section: Discussionsupporting
confidence: 91%
“…Firstly, in our study, the ultrasound-guided method was roughly consistent with that reported by Johnston et al [ 16 ]. Local, clear ultrasonograms were obtained by Johnston et al [ 16 ], who used high-frequency probes. In our study, significant thickening of subcutaneous soft tissues in the sacrococcygeal area in obese patients prevented clear visualization of the sacrococcygeal joint because of insufficient penetration of the ultrasound waves when using a high-frequency probe.…”
Section: Discussionsupporting
confidence: 91%
See 1 more Smart Citation
“…Ganglion Impar or Walther is an unpaired structure located at the termination of bilateral lumbosacral sympathetic chains and supplies nociceptive and sympathetic fibers to the perineum, distal rectum, perianal region, distal urethra, vulva/scrotum, and the distal third of the vagina. [ 72 73 74 ] It is a retroperitoneal structure located at or slightly below (up to 2 cm) the sacrococcygeal junction. [ 75 ] It is the sustained visceral sympathetically mediated perineal pain which is amenable for ganglion impar block.…”
Section: Interventional Pain Management Guidelines According To Clinimentioning
confidence: 99%
“…[ 79 ] Other approaches described in the literature include transsacrococcygeal and transdiscal approach. [ 72 80 ] However, fluoroscopic confirmation of retroperitoneal needle tip location and appropriate dye spread (Comma sign produced by 1–2 ml of radiographic contrast medium) is a must before injection of neurolytic agents (6% phenol) when USG is used as the primary imaging modality. [ 72 79 81 ] The closer the needles tip to the rectum, the lower the volume of neurolytic agent (1–8 ml) that should be injected.…”
Section: Interventional Pain Management Guidelines According To Clinimentioning
confidence: 99%